Rates of convergence in normal approximation under moment conditions via new bounds on solutions of the Stein equation - Gaunt, R (Springer, 2014)
New bounds for the (Formula presented.)th-order derivatives of the solutions of the normal and multivariate normal Stein equations are obtained. Our general order bounds involve fewer derivatives of the test function than those in the existing literature. We apply these bounds and local approach couplings to obtain an order (Formula presented.) bound, for smooth test functions, for the distance between the distribution of a standardised sum of independent and identically distributed random variables and the standard normal distribution when the first (Formula presented.) moments of these distributions agree. We also obtain a bound on the convergence rate of a sequence of distributions to the normal distribution when the moment sequence converges to normal moments.